Invasive vs Conservative Management of Patients With Chronic Total Occlusion: Results From the ISCHEMIA Trial - Bangalore, Sripal; Mancini, G B John; Leipsic, Jonathan; Budoff, Mathew J; Xu, Yifan; Anthopolos, Rebecca; Brilakis, Emmanouil S; Dwivedi, Aeshita; Spertus, John A; Jones, Phil G; Cho, Yoon Joo; Mark, Daniel B; et al. (Elsevier BV, 2025)
Randomized trials of chronic total occlusion (CTO) revascularization vs medical therapy have yielded inconsistent results.